Development and psychometric testing of the Professional Interpersonal Competency Assessment Scale for Novice nurses (PICASN) - Yuko Sato; Yuko Yasuhara; Hirokazu Ito; Gil P. Soriano; Allan Paulo Blaquera; Rozzano Locsin; Tetsuya Tanioka (Belitung Raya Foundation, Indonesia, 2023)
Background: Assessing the professional interpersonal competency of novice nurses is crucial for preventing staff turnover and promoting effective work. However, none of the instruments identified in the literature specifically target novice nurses. Objective: This study aimed to develop and psychometrically test the perception dimension of the Professional Interpersonal Competency Assessment Scale for Novice nurses (PICASN) in Japan. Methods: The study comprised four steps: 1) concept identification, 2) item construction, 3) validity measure, and 4) reliability measure. A cross-sectional web-based questionnaire was administered from February to April 2023 and was completed by 203 novice nurses. Data quality was assessed using mean, item response, missing values, floor and ceiling effects, internal consistency, and item-rest correlations. Content validity index (CVI) was used to determine the instrument’s validity, while exploratory factor analysis (EFA) using maximum likelihood estimation with Promax rotation was employed to assess the factor structure. Cronbach’s alpha was used to evaluate reliability. Results: The 27-item PICASN demonstrated an Item-CVI of 0.94 and a Scale-CVI of 0.88. EFA revealed two factors: 1) Basic competencies as a novice nurse (15 items) and 2) Relationship building skills within the healthcare team (12 items), which explained 80% of the variance. Internal consistency reliability was excellent at 0.94 and 0.91 for the factors, and the overall scale reliability was 0.95. The item-rest (I-R) correlation values exceeding 0.6 were considered acceptable. Conclusion: The PICASN demonstrates satisfactory psychometric properties, making it an effective tool for measuring professional interpersonal competency among novice nurses in Japan. This instrument serves to assist novice nurses by promoting self-awareness and offering targeted insights into specific areas requiring improvement. Additionally, it provides experienced nurses and nurse managers with valuable insights into team dynamics, guiding interventions for continuous quality improvement.